Characterisation of optical phonons within epitaxial Ge2Sb2Te5/InAs(111) structures. (1st August 2022) - Alsaigh, R.A.; Shelford, L.R.; Mohamad, H.J.; Shalini, A.; Al-Jarah, U.A.S.; Bragaglia, V.; Giussani, A.; Calarco, R.; Srivastava, G.P.; Hicken, R.J.
Abstract: Femto-second pump-probe and micro-Raman spectroscopy (RS) measurements have been made to identify optical phonons in Ge2 Sb2 Te5 /InAs(111) and an InAs(111) substrate. A theory of transient stimulated Raman scattering (TSRS) incorporating the Raman tensor predicts which phonon modes may be observed in transient reflectance (R) and anisotropic reflectance (AR) pump-probe measurements, and how their amplitudes depend upon angles φ and θ that describe the orientation of the pump and probe beam electric fields within the sample plane. AR measurements of an InAs(111) substrate revealed the 6.5 THz T 2 transverse optical phonon with amplitude proportional to sin(2(θ − φ)), as expected for both TSRS and the specular optical Kerr effect (SOKE), confirming that TSRS and SOKE are equivalent descriptions of the same phenomenon. The AR responses of Ge2 Sb2 Te5 /InAs(111) revealed a single coherent optical phonon (COP) mode at about 3.4 THz with sin(2(θ − φ)) amplitude variation that confirms the T 2 -like character of the mode and hence the underlying cubic structure of the epilayer. This mode was also observed in the R measurement for one sample, with amplitude independent of φ and θ as predicted by TSRS theory. Both R and AR signals were heavily damped, which is attributed to dephasing of T 2 x, T 2 y and T 2 z modes that become non-degenerate due to structural distortions. RS measurements revealed three modes for Ge2 Sb2 Te5 /InAs(111) and three modes for InAs(111). Taken together the TSRS and RS measurements provide rich information about optical phonons in the phase change material Ge2 Sb2 Te5 and the InAs(111) surface. Highlights: Coherent optical phonons are observed in Ge2 Sb2 Te5 /InAs(111) thin films. Coherent optical phonons are excited by transient stimulated Raman scattering. Optical polarisation dependence of coherent phonons confirms cubic crystal structure. Damping of phonon oscillations is due to dephasing of 3 nearly degenerate modes.